The New Fate of Peasants - Zhao, Shukai (Springer Singapore, 2018)
This book discusses the historical transformation of the destiny of Chinese peasants under the contemporary political economic conditions, and tries to explore the institutional mechanism behind the formation and maintenance of these conditions. The analysis focuses on the consequences of the great social mobilization brought about by the reform. The phenomenon of migrant workers is the most significant consequence of the change of Chinese peasants' life courses. The destiny of migrant workers will be the destiny of Chinese peasants. The introduction chapter of this book discusses the historical context and peasants' fates, their political participation, and citizenship of peasants after they become urban dwellers. Chapter one discusses the social implication and economic consequences of the urbanization of rural population. Chapter two discusses the living conditions for peasants that moved to work in cities, including working environments, living environments, education of their children, and their social networking. Chapter three discusses the challenges that the mobilization of peasants has posed on government policy making and urban managements. Chapter four discusses the latest development in the social mobilization of Chinese peasants.